Factors Contributing to Fraudulent Practices in Construction Project Life Cycle - Amylia Izrin Mohd Saim, Nur; Abdul Rahman, Ismail; Firdaus Ismail, Mohd (International Journal of Engineering and Technology, 2018)
This article managed to identify and complie factors contributing to fraudulent practices throughout the construction project life cycle from many research works conducted globally on fraudulent practices in the construction industry. These extracted fraudulent factors were mapped in the matrix form to check for the similarity among the factors. Finally, 42 contributing factors were accepted are parked into 5 stages of Construction Project Life Cycle. After checking frequency, the major factor for every stage are getting project approval in planning stage; collusion between tenderer and public officer in design and tendering stage; inadequate compliance with design for audit and report in construction stage; avoidance of difficulties in contract inspection in finishing stage and finally using substandard materials and services in maintenance stage. Â Â Â Â Â Â Â Â